2017
DOI: 10.1002/brb3.638
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral cochlear implants: Developmental advances do not yet achieve normal cortical processing

Abstract: BackgroundSimultaneous bilateral cochlear implantation promotes symmetric development of bilateral auditory pathways but binaural hearing remains abnormal. To evaluate whether bilateral cortical processing remains impaired in such children, cortical activity to unilateral and bilateral stimuli was assessed in a unique cohort of 16 children who received bilateral cochlear implants (CIs) simultaneously at 1.97 ± 0.86 years of age and had ~4 years of CI experience, providing the first opportunity to assess electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 85 publications
(173 reference statements)
4
26
1
1
Order By: Relevance
“…Such asymmetries evident in physiological measurements often parallel asymmetries observed in behavioral tasks, such as speech perception in quiet (e.g., Gordon and Papsin, 2009;Jiwani et al, 2016), spatial unmasking (Chadha et al, 2011), and lateralization to interaural timing differences (Gordon et al, 2014). These abnormal asymmetries can be prevented by providing two CIs early in life, simultaneously or with minimal interimplant delay (Gordon et al, 2013;Easwar et al, 2017); this is the current recommended standard of care in children with bilateral deafness (Ramsden et al, 2012). In support, none of the children with simultaneously received CIs or those with short interimplant delays demonstrated asymmetries as large as those evident in children with long interimplant delays ( Figure 4C and D).…”
Section: Consistent CI Use Is Important To Promote Optimal Speech Permentioning
confidence: 90%
See 2 more Smart Citations
“…Such asymmetries evident in physiological measurements often parallel asymmetries observed in behavioral tasks, such as speech perception in quiet (e.g., Gordon and Papsin, 2009;Jiwani et al, 2016), spatial unmasking (Chadha et al, 2011), and lateralization to interaural timing differences (Gordon et al, 2014). These abnormal asymmetries can be prevented by providing two CIs early in life, simultaneously or with minimal interimplant delay (Gordon et al, 2013;Easwar et al, 2017); this is the current recommended standard of care in children with bilateral deafness (Ramsden et al, 2012). In support, none of the children with simultaneously received CIs or those with short interimplant delays demonstrated asymmetries as large as those evident in children with long interimplant delays ( Figure 4C and D).…”
Section: Consistent CI Use Is Important To Promote Optimal Speech Permentioning
confidence: 90%
“…On the contrary, several studies have shown a lack of difference in outcomes between CIs in children with simultaneously received devices (Gordon and Papsin, 2009;Easwar et al, 2017) and in adults with unilateral implants in the right/left ear (Morris et al, 2007;Budenz et al, 2011 [younger adults group]). While the lack of an observable right ear advantage could be due to smaller sample sizes in previous studies in children (Gordon and Papsin, 2009: n 5 6; Easwar et al, 2017: n 5 16) relative to the present study (n 5 25), this is less likely the case with studies in adults with larger samples (Morris et al, 2007: right CI n 5 63, left CI n 5 38; Budenz et al, 2011 [younger adults group]: right CI n 5 29, left CI n 5 19).…”
Section: Children With Simultaneously Received Cis Demonstrate a Righmentioning
confidence: 99%
See 1 more Smart Citation
“…The time-restricted, artefact and coherent source suppression (TRACS) linearly constrained minimum variance type beamformer ( Wong and Gordon, 2009 ) was used to estimate source dipole activity underlying latency windows encompassing the first visually identified positive (P1) and negative (N2) peaks of the immature cortical waveform ( Fig. 2 ), as previously described ( Easwar et al, 2017a , Gordon et al, 2013b , Gordon et al, 2010 ). Briefly, application of the time-restricted artefact suppression algorithm maintained evoked responses while suppressing ~ 97% of the CI artefact corresponding to the four largest singular vector values between − 80 to 10 ms ( Wong and Gordon, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Stimuli were presented at 50 dB above behavioral threshold (dB SL) and the order of click and tone‐burst presentation was counter balanced. As in previous studies (Easwar, Yamazaki, Deighton, Papsin, & Gordon, ), EEG responses from 62 cephalic electrodes referenced to the right earlobe were recorded using NeuroScan v4.5 with a Synamps‐II amplifier during passive listening (Compumedics USA, Inc., Charlotte, NC). Participants watched a silent subtitled movie, read a book, or played games on a tablet with minimal movement.…”
Section: Methodsmentioning
confidence: 99%